2016
DOI: 10.1002/hed.24183
|View full text |Cite
|
Sign up to set email alerts
|

Descending necrotizing mediastinitis: Systematic review on its treatment in the last 6 years, 75 years after its description

Abstract: For mediastinitis limited to the upper part of the mediastinum, transcervical drainage may be sufficient; cases that extended below the tracheal carina may require cervical and transthoracic drainage. A multidisciplinary therapeutic approach has allowed a reduction in its mortality. © 2016 Wiley Periodicals, Inc. Head Neck 38: E2275-E2283, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 42 publications
5
108
0
8
Order By: Relevance
“…Although no guidelines or published articles have reported high-level evidence on the treatment of DNM, the need for integration of a multidisciplinary team is strongly recommended. 3 The primary treatment of DNM includes intravenous broad-spectrum antibiotics, airway management, surgical restoration of the pharyngeal or dental focus, and adequate drainage of the neck and mediastinum. 2 Septicaemia with the possibility of toxic shock, impaired haemodynamics, and pleuropulmonary infections are frequently observed in the early postoperative stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although no guidelines or published articles have reported high-level evidence on the treatment of DNM, the need for integration of a multidisciplinary team is strongly recommended. 3 The primary treatment of DNM includes intravenous broad-spectrum antibiotics, airway management, surgical restoration of the pharyngeal or dental focus, and adequate drainage of the neck and mediastinum. 2 Septicaemia with the possibility of toxic shock, impaired haemodynamics, and pleuropulmonary infections are frequently observed in the early postoperative stages.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our study showed that similar to the conventional approach, VATS with or without catheter interventional therapy can achieve a low mortality rate in patients with type II DNM. 3,24 Hyperbaric oxygen therapy is believed to have a significant survival benefit in patients with necrotizing fasciitis, limiting the extent and number of surgical debridement procedures. 2,28 In the present study, hyperbaric oxygen was not used because its benefits remain controversial 29 ; the treatment itself disturbs other procedures in the acute stage, 12,21 and no consensus protocol for treatment implementation exists.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Descending necrotizing mediastinitis describes a serious infective process that originates from the ears, nose or throat and spreads inferiorly into the mediastinum via connective-tissue planes. It can be defined by the presence of a severe oropharyngeal infection with concurrent radiological features that suggest mediastinitis [20,21]. As with other forms of mediastinitis, DNM can be classified into Type I (localized), Type IIa (diffuse, extending into the lower anterior mediastinum) and Type IIb (diffuse, extending into both the anterior and posterior lower mediastinum) [22] (Fig.…”
Section: Descending Necrotizing Mediastinitismentioning
confidence: 99%
“…Odontogenic inflammatory disorders and infections which comes from nasopharynx, cause neck and mediastinum bacterial infections, and are life-threatening not only among patients with comorbidities or immunity loss in HIV or immunosuppression, but also, like has been presented in two described cases, among patients without past medical history. In presented cases have not confirmed to 47%) then pharyngeal (33% to 45%), cervical (15%), and other head and neck infections (5%) [6]. In two described cases, the teeth were the etiological factor of the DNM.…”
Section: Resultsmentioning
confidence: 65%